What are anniversaries for? On the need for an interpretive reading of Peruvian architecture - Montestruque Bisso, Octavio (2023)
This article proposes a reflection on the importance of undertaking processes of interpre- tation of the architectural legacy in Peru, using a serious and informed methodology that allows us to take a global position without ceasing to be ourselves. For this, it is impor- tant to understand the importance of criticism as a fundamental input to stimulate ideas and leave aside some a priori and superficial readings.